PENGARUH LEVERAGE DAN KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA DENGAN AGENCY COST SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR - Rahyuningsih Rahyuningsih; Sri Ayem (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2020)
This study aims to compare the leverage and managerial ownership of earningsmanagement with agency cost as an intervening variable. This study took apopulation of several companies listed on IDX and the number of samples in thisstudy were 16 companies, the sample technique used was purposive sampling.The data analysis method used is the path analysis. The results of this studyafter testing the first stage showed simultaneously that leverage and managerialownership affect agency cost and testing the second stage of leverage, managerialownership and agency cost affect earnings management. Partially through the ttest, in the first stage of testing that leverage affects agency cost and managerialownership does not affect agency cost. The second stage of testing that leveragedoes not affect earnings management, managerial ownership does not affectearnings management and agency costs affect earnings management.